PENGARUH BEBAN PAJAK PENGHASILAN BADAN DAN PROFITABILITAS TERHADAP LABA BERSIH PADA PERUSAHAAN SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA 2020-2023 - Sapitri; Iqbal, Johandri; Saputra, Ferdyan Wana (Journal of Applied Accounting And Business, 2025)
This research aims to determine the extent of the influence of income tax burden and profitability on net profit. The population used in this research is palm oil companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. Determining the sample in this study was purposive sampling, with a sample of 10 companies. The type of data used in this research is quantitative data. The measuring tool used for this analysis is the SPSS Version 25.0 program. This research uses the classical assumption test, multiple linear regression analysis test, R2 coefficient of determination test, and hypothesis test. The results of this research are based on (t test) corporate income tax burden (X1) has an effect on net profit partially while profitability (X2) has no effect on net profit partially. (F test) Together the corporate income tax burden and profitability have an effect on net profit.